2016
DOI: 10.1080/21711976.2016.1138667
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions that explain attachment to the home / Dimensiones que explican el apego a la vivienda

Abstract: The home is the central place in a person's life, in relation to which they develop strong bonds of attachment. The living room is the most public and representative space of the home. This article aims to ascertain the extent to which attachment to the home is related with control and place identity. It also studies the extent to which the representativeness of the living room is explained by the descriptive and connotative dimensions attributed to it by the resident. To achieve these aims, 50 participants, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
6
0
4
Order By: Relevance
“…The literature describing research on individuals in relation to their residential environments has addressed various spatial levels applicable to the term “residential” ( Marans, 2003 ), from the micro to the macro level (see also Bonaiuto & Alves, 2012 ; Lewicka, 2010 ), from the single dwelling (e.g., Gomez-Jacinto & Hombrados-Mendieta, 2002 ; Pasca, Aragones, & Poggio, 2016 ; Anton & Lawrence, 2014 ) to the residential complex or facility (e.g., Cerina, Fornara, & Manca, 2017 ), the neighborhood (e.g., Hernández, Hidalgo, Salazar-Laplace, & Hess, 2007 ; Fleury-Bahi, Félonneau, & Marchand, 2008 ; Bonaiuto, Fornara, Ariccio, Cancellieri, & Rahimi, 2015 ; Fornara, Lai, Bonaiuto, & Pazzaglia, 2019 ), and the broader urban context (e.g., Brown & Kytta, 2014 ; Casakin, Hernandez, & Ruiz, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature describing research on individuals in relation to their residential environments has addressed various spatial levels applicable to the term “residential” ( Marans, 2003 ), from the micro to the macro level (see also Bonaiuto & Alves, 2012 ; Lewicka, 2010 ), from the single dwelling (e.g., Gomez-Jacinto & Hombrados-Mendieta, 2002 ; Pasca, Aragones, & Poggio, 2016 ; Anton & Lawrence, 2014 ) to the residential complex or facility (e.g., Cerina, Fornara, & Manca, 2017 ), the neighborhood (e.g., Hernández, Hidalgo, Salazar-Laplace, & Hess, 2007 ; Fleury-Bahi, Félonneau, & Marchand, 2008 ; Bonaiuto, Fornara, Ariccio, Cancellieri, & Rahimi, 2015 ; Fornara, Lai, Bonaiuto, & Pazzaglia, 2019 ), and the broader urban context (e.g., Brown & Kytta, 2014 ; Casakin, Hernandez, & Ruiz, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A significant body of research on place attachment has evaluated these characteristics to establish whether they have an impact on the socio-physical bond formed, and interestingly, the results have been very varied. While some studies show that home ownership and the number of years living in a place are aspects that increase involvement with the social network and sense of belonging (Anton & Lawrence, 2014; Pasca et al, 2016; Vidal et al, 2010), in other studies, these aspects are not found to be significant or conclusive (Gurney et al, 2017; Málovics et al, 2019; Manzo, 2014).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, Pasca et al (2016) established that people develop very strong affective bonds with their homes, and gender-sensitive studies emphatically underscore the benefits of home ownership for individuals and communities. For example, it increases citizen participation, makes local business more sustainable and promotes a sense of security and comfort (Rubio & Coronel, 2018)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of neighborhood characteristics on the experiences deriving from people’s interaction with their place of residence and, in particular, on residents’ health, well-being and satisfaction with their neighborhoods, has been widely studied in environmental psychology (Hur and Morrow-Jones, 2008; Oktay et al, 2012; Bonaiuto et al, 2015; Wheaton et al, 2015; Pasca et al, 2016; Lekkas et al, 2017). In order to explain the influence of neighborhood attributes, the authors refer to the role played by the objectively defined characteristics, residents’ perceptions, and the distinction between the objective and perceived characteristics of the environment that influence the positive or negative assessment made by residents.…”
Section: Introductionmentioning
confidence: 99%